Contemporary world regional geography : - Bradshaw, Michael (McGraw-Hill Higher Education, 2004)
This book is the product of the hard work and dedication of dozens og people, all of whom shared a commongoal: to produce the very best world regional geography book possible. No single person, no matter how educated, "knows" everything about the world's regions. Even an author team whose collective expertise covers most of the field must rely on an almost unimaginable amount of feedback. The manuscript for this text went through three full draft revisions, along with rigorous reviewing by instructors. As we examined every word of text in the book, we also scrutinized every piece of art with a critical look at how it works with the text. An advisory panel was established to help us refine the text and art; a focus group was held to critique the market, text, supplements.